2017
DOI: 10.3892/or.2017.5537
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA-194 regulates human melanoma cells via PI3K/AKT/FoxO3a and p53/p21 signaling pathway

Abstract: In the present study, we analyzed the role of microRNA-194 circulating regulated human melanoma cell growth. We found that microRNA-194 expression was markedly suppressed in human melanoma patients, compared with negative control group. Next, disease-free survival (DFS) and overall survival (OS) of high expression in human melanoma patients was higher than those of low expression in human melanoma patients. MicroRNA-194 overexpression inhibited cell proliferation, induced apoptosis, increased caspase-3/−9 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…36 Studies have also shown that FOXO3A, as a tumor-suppressor gene, could induce the expressions of pro-apoptotic genes. 37,38 Thus, LY294002 may reverse the effects of HAX-1 on cell proliferation and migration by regulating the phosphorylation of relevant subunits (p110 and p85) or the expressions of downstream regulatory proteins (FOXO3A) in PI3K/Akt. In mammals, FOXO3A is involved in the development and progression of tumors by regulating survivin, p27, p21, and vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies have also shown that FOXO3A, as a tumor-suppressor gene, could induce the expressions of pro-apoptotic genes. 37,38 Thus, LY294002 may reverse the effects of HAX-1 on cell proliferation and migration by regulating the phosphorylation of relevant subunits (p110 and p85) or the expressions of downstream regulatory proteins (FOXO3A) in PI3K/Akt. In mammals, FOXO3A is involved in the development and progression of tumors by regulating survivin, p27, p21, and vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, miR-194 also exerted its anti-proliferative effect on osteosarcoma cells via CDH2 and IGF1R [19]. Furthermore, miR-194 exhibited proapoptotic effect on melanoma cells by modulating PI3K/AKT/FoxO3a and p53/p21 signaling pathway [9].…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al reported that overexpression of miR-194 can inhibit migration and invasion in glioma cells [8]. Moreover, the proliferation of melanoma cells was suppressed by miR-194 overexpression [9]. However, the specific role of miR-194 in NSCLC and further underlying mechanisms have yet not been unveiled.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence continues to increase in the majority of the population [1][2][3]. It often shows a poor response to radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%